2021
DOI: 10.3390/healthcare9010051
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Antibodies to SARS-CoV-2 among Blood Donors during COVID-19 Lockdown: A Study from Saudi Arabia

Abstract: In response to the coronavirus disease 2019 (COVID-19), Saudi Arabia have imposed timely restrictions to minimize the infection spread, lower the risk for vulnerable groups, and reduce the pressure on healthcare services. The effectiveness of these measures has not been assessed comprehensively and, thereby, remains uncertain. Besides monitoring the number of COVID-19 cases diagnosed by molecular assays, the seroprevalence can serve as an indicator for the incidence rate among the general population. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Non-COVID patients had a trend of higher seroprevalence than blood donors. This is likely due to their co-morbid conditions as previous studies suggested that comorbidities are risk factors for COVID-19, partially as a result of increased expression of ACE-2, the SARS-CoV-2 host-cell receptor [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-COVID patients had a trend of higher seroprevalence than blood donors. This is likely due to their co-morbid conditions as previous studies suggested that comorbidities are risk factors for COVID-19, partially as a result of increased expression of ACE-2, the SARS-CoV-2 host-cell receptor [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was significant heterogeneity by methodological factors that influence seroprevalence estimates (Table 1, summarized by Figure 5). Characterization of the blood donor populations varied; five studies did not report the age of donors sampled [16,23,38,39,41]. The scope of studies varied, the majority (76%; 25/33) provided regional estimates within countries.…”
Section: Resultsmentioning
confidence: 99%
“…We previously developed and optimized an S-based ELISA that enables sensitive and specific detection of SARS-CoV-2 IgG antibody in human sera [ 18 ]. This protocol was subsequently applied in a number of seroprevalence studies [ 19 , 20 ]. Currently, the number of people who are receiving COVID-19 vaccination is escalating.…”
Section: Introductionmentioning
confidence: 99%